2018
DOI: 10.1088/1674-1056/27/9/094211
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement and control of the Goos—Hänchen shift by nonlinear surface plasmon resonance in graphene

Abstract: The Goos-Hänchen (GH) shift of graphene in the terahertz frequency range is investigated, and an extremely high GH shift is obtained owing to the excitation of surface plasmon resonance in graphene in the modified Otto configuration. It is shown that the GH shift can be positive or negative, and can be enhanced by introducing a nonlinearity in the substrate. Large and bistable GH shifts are demonstrated to be due to the hysteretic behavior of the reflectance phase. The bistable GH shift can be manipulated by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The existence of the GH shift was confirmed by experiments in 1947 by Goos and Hänchen [1,2]. There has been a great deal of theoretical and experimental [3][4][5][6][7][8][9] research since the discovery and confirmation of the effect. Usually, the GH shift between two interfaces is very small, almost comparable to the wavelength, which makes it difficult to observe and measure experimentally.…”
Section: Introductionmentioning
confidence: 79%
“…The existence of the GH shift was confirmed by experiments in 1947 by Goos and Hänchen [1,2]. There has been a great deal of theoretical and experimental [3][4][5][6][7][8][9] research since the discovery and confirmation of the effect. Usually, the GH shift between two interfaces is very small, almost comparable to the wavelength, which makes it difficult to observe and measure experimentally.…”
Section: Introductionmentioning
confidence: 79%
“…[4][5][6] The GH and IF effects have attracted wide attention in physics and have been studied at different interfaces in recent decades, such as hybridized topological insulator, [7] metasurface, [8,9] photonic crystal, [10,11] temporally dispersion attenuation material, [12] graphene. [13][14][15][16][17][18][19] Specifically in these studies, GH and IF shifts were tuned by magnetic field and chemical potential, [7,[17][18][19] and often used as effective probes in precision metrology of material structural parameters since they were sensitive to material properties. [15,16] Weyl semimetal (WSM), an emerging topological material who takes non-mass Weyl fermions as quasi-particles, is also known as "three-dimensional graphene".…”
Section: Introductionmentioning
confidence: 99%
“…Strikingly this approach allows complete electrostatic control [17,18]. Recently it has been shown that nonlinear surface plasmon resonance in graphene can provide rigorous enhancement and control over GH effect [19,20].…”
Section: Introductionmentioning
confidence: 99%